Germanium nanoislands grown by radio frequency magnetron sputtering grown germanium nanoislands: annealing time dependent surface morphology and photoluminescence - Othaman, Zulkafli (IOP Publishing Ltd., 2013)
Structural and optical properties of ~ 20 nm Ge nanoislands grown on Si(100) by radio frequency (rf) magnetron sputtering under varying annealing conditions are reported. Rapid thermal annealing at a temperature of 600°C for 30 s, 90 s, and 120 s are performed to examine the influence of annealing time on the surface morphology and photoluminescence properties. X-ray diffraction spectra reveal prominent Ge and GeO2 peaks highly sensitive to the annealing time. Atomic force microscope micrographs of the as-grown sample show pyramidal nanoislands with relatively high-density 1011 cm-2)). The nanoislands become dome-shaped upon annealing through a coarsening process mediated by Oswald ripening. The room temperature photoluminescence peaks for both as-grown 3.29 eV) and annealed 3.19 eV) samples consist of high intensity and broad emission, attributed to the effect of quantum confinement. The red shift (~0.10 eV) of the emission peak is attributed to the change in the size of the Ge nanoislands caused by annealing. Our easy fabrication method may contribute to the development of Ge nanostructure-based optoelectronics.